Knowledge, attitudes, and practices on the prevention of intestinal Schistosomiasis in rural areas of Kimpese, Democratic Republic of the Congo - Anderson M. Munenge; Henry-Jacques M. Bomoi; Fiston B. Masikini; Becker T. Kanku; Prescillia P. Mabubu; Dénise W. Okito; Jean-Jacques D. Amogu; Odette N. Kabena; Thierry T. Tangou (Orapuh Journal)
Introduction